(untitled) (World Bulletin of Public Health, 2026)
Over the past several decades, the relationship between environmental factors and human health has become a central topic in global scientific discourse. Increasing industrialization, rapid urbanization, climate change, and pollution have intensified concerns about how environmental degradation affects public health. Within this context, environmental knowledge—often referred to as environmental literacy or awareness—has emerged as a critical determinant of individual and community health behaviors. Researchers across different countries have explored how awareness of environmental issues influences lifestyle choices, risk perception, and preventive health practices.